B cell Compartmentalisation in Blood and Cerebrospinal Fluid of HIV- Infected Ugandans with Cryptococcal Meningitis - Okurut, Samuel; Meya, David B; Olobo, Joseph; Bohjanen, Paul R; Bwanga, Freddie; Eller, Michael A; Boulware, David; Kathy Huppler Hullsiek; Pratap, Harsh; Manabe, Yukari C; Palmer, Brent; Janoff, Edward; et al. (bioRxiv, 2019)
Background: Activated B cells modulate infection by differentiating into pathogen-specific antibody-producing effector plasmablasts/plasma cells, memory cells and immune regulatory B cells. In this context, the B cell phenotypes that infiltrate the central nervous system during HIV and cryptococcal meningitis co-infection are ill defined. Methods: We characterised clinical parameters, mortality and B cell phenotypes in blood and CSF by flow cytometry in HIV-infected adults with cryptococcal (n=31), and non-cryptococcal meningitis (n=12), and heathy control subjects with neither infection (n=10). Results: Activation of circulating B cells (CD21low) was significantly higher in blood of subjects with HIV infection compared with healthy controls, and greater yet in matched CSF B cells (p<0.001). Among B cell subsets, elevated frequencies of memory and plasmablasts/plasma cells most clearly distinguished the CSF from blood compartments. With cryptococcal meningitis, lower frequencies of expression of the regulatory protein PD-1 on plasmablasts/plasma cells in blood (median 7%) at presentation was associated with significantly decreased 28-day survival (29% (4/14 subjects)), whereas higher PD-1 expression (median 46%) characterised subjects with higher survival (88% (14/16 subjects)). Conclusion: With HIV infection, B cell differentiation and regulatory markers are discrete elements of the circulating and CSF compartments with clinical implications for cryptococcal disease outcome, potentially due to their effects on the fungus and other local immune cells.